La Inversión Acertada en la Educación Superior como Desarrollo Sostenible - Garcés Garcés, Norma Narcisa (2016)
The development of education is a new proposal that seeks to articulate a number of thematic areas that are interrelated and are developing jointly, is an opportunity to find and make sense of educational processes through the environment, rights human, gender, rural development, multiculturalism and peace. The construction of another possible world, is an education for life that allows you to prepare to solve problems of everyday,professional and spiritual life, and is immersed human rights, social, economic and political, responds to the great nature problems.Current education systems are vertical and are very focused on without solidarity and competitiveness are instruments of unsustainability. People and society must begin to reflect deeply on the destruction of the planet, educate and build a more sustainable and environment friendly life; it must reflect deeply how education systems is built.Investing in education is the most successful in the present and future because it prevents poverty is transmitted from generation to generation and offers better employment opportunities.